The name of this book is secret - Bosch, Pseudonymous; Ford, Gilbert (New York : Little, Brown, 2008)
Two eleven-year-old misfits try to solve the mystery of a dead magician and stop the evil Dr. L and Ms. Mauvais, who are searching for the secret of immortality.
Reprint. Originally published: 2007.
810
Accelerated Reader AR
Keywords: Immortality -- Juvenile fiction; Adventure and adventurers -- Fiction; Immortality -- Fiction